Chronic urticaria and the gut microbiota: what is this 'long-distance' relationship? - Ser, Hooi Leng *; Wong, Joshua You Jing *; Goh, Bey Hing *; Kavita, Reginald *; Raja Affendi, Raja Ali * (BMJ Publishing Group, 2023)
Background Chronic urticaria is characterized by daily itchy wealing of the skin for more than six weeks, affecting roughly 0.5 – 2% of the global population. Although the precise causes of chronic urticaria are not usually known, it has been suggested that this condition may arise due to autoimmune disorders, allergies, infections, or medications. The gut microbiome plays an important role in immune regulation and its effects in many immune-mediated diseases have been reported. Consequently, this work investigates the distinctive gut microbiota changes in chronic urticaria and the potential of identifying biomarkers or therapeutic targets to facilitate disease diagnosis/treatment.